A experiência de Samuel Beckett no cinema - Reis, Adriel Diniz dos (2021)
This thesis presents a cinematographic analysis of the short film named Film (1965) from the perspective of theatrical influence the Irish Samuel Beckett. Thus, this work brings together the film Film, the play Waiting for Godot and all the dramaturgical work written by the Irish playwright Beckett. Written and directed by Beckett and co-directed by the American stage director Alan Schneider, Film addresses the Irish philosopher George Berkeley’s “To be is to be perceived” principle. In turn, Waiting for Godot, Beckett's main play, approaches the conceptual tripod of all Beckettian dramaturgy, based on the concepts of time, memory and habit, so important to the French writer Marcel Proust. Therefore, this research is interested in discussing the “subjective self-performances” raised in the reader-viewer from the relationships established in the filmic-theatrical characters' plot of the beckettian.